1975
DOI: 10.1677/joe.0.0660085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous and Intracarotid Injections of Hypertonic Fluids on the Release of Melanocyte-Stimulating Hormone From the Rat Posterior Pituitary Lobe Incubated in Situ

Abstract: The posterior pituitary lobe of male rats under urethane anaesthesia was incubated in situ. The pituitary gland was exposed by thr transpharyngeal apprach. The posterior lobe remained in neural and partial vascular connexion with the hypothalamus, whereas the anterior lobe was entirely remobed. Incubation fluid was collected and its melanophore-stimulating activity was assayed in hypophysectomized frogs. No effect was observed after the i.v. injection of 1 ml 120 muM-NaC1 with 60 muM-CaC12 or isotonic NcC1 sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Administration of hypertonic saline in drinking water has been reported to activate the hypothalamic-neurohypophyseal axis, pro ducing an increase in the turnover of neural lobe hormones oxytocin and vasopressin [Gilman and Goodman, 1937;Friesen and Astwood, 1967;Jones and Pickering, 1969;Kleeman and Vorherr, 1974], as well as activation of MSH release [Howe and Thody, 1970;Taleisnik et al, 1972;Cyrkowicz and Traczyk, 1975]. We found that this stimulus depleted both anterior and neurointermediate lobe END levels in a significant majority of the animals after varying periods of salt loading.…”
Section: Discussionmentioning
confidence: 63%
“…Administration of hypertonic saline in drinking water has been reported to activate the hypothalamic-neurohypophyseal axis, pro ducing an increase in the turnover of neural lobe hormones oxytocin and vasopressin [Gilman and Goodman, 1937;Friesen and Astwood, 1967;Jones and Pickering, 1969;Kleeman and Vorherr, 1974], as well as activation of MSH release [Howe and Thody, 1970;Taleisnik et al, 1972;Cyrkowicz and Traczyk, 1975]. We found that this stimulus depleted both anterior and neurointermediate lobe END levels in a significant majority of the animals after varying periods of salt loading.…”
Section: Discussionmentioning
confidence: 63%
“…Since these early reports, other investigators have found that hydromineral imbalance results in a histological appearance of PI cells suggestive of hyperactivity 20 and an increase in aMSH secretion. 21 Levitin et al 22 showed that rats bearing PI transplants had heightened natriuretic responses to volume loads. Releasing factors for PI hormones, such as serotonin agonists 23 or corticotropin-releasing factor, 24 appear to produce centrally mediated natriuresis.…”
mentioning
confidence: 99%